2012
DOI: 10.1063/1.3665717
|View full text |Cite
|
Sign up to set email alerts
|

Studying enzymatic bioreactions in a millisecond microfluidic flow mixer

Abstract: In this study, the pre-steady state development of enzymatic bioreactions using a microfluidic mixer is presented. To follow such reactions fast mixing of reagents (enzyme and substrate) is crucial. By using a highly efficient passive micromixer based on multilaminar flow, mixing times in the low millisecond range are reached. Four lamination layers in a shallow channel reduce the diffusion lengths to a few micrometers only, enabling very fast mixing. This was proven by confocal fluorescence measurements in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Babich et al demonstrated the possibility of gram scale synthesis of phosphorylated compounds using phosphatase immobilized on Immobeads [34]. Buchegger et al used a microfluidic mixer to study the pre-steady state development of an enzymatic bioreaction and found that the dynamics of a biochemical reaction can be studied in a few seconds [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Babich et al demonstrated the possibility of gram scale synthesis of phosphorylated compounds using phosphatase immobilized on Immobeads [34]. Buchegger et al used a microfluidic mixer to study the pre-steady state development of an enzymatic bioreaction and found that the dynamics of a biochemical reaction can be studied in a few seconds [35]. …”
Section: Introductionmentioning
confidence: 99%
“…5,6,13,[20][21][22][23] The technique uses co-flow of miscible focusing solution to confine a solution to a sub-cross-section of a channel. Groups develop various hydrodynamic focusing architectures for mitigating sticking to channel walls, 6 ensuring rapid mixing, 13,24,25 and ensuring uniform residence time among the focused solutes. 13,21,22 Three-dimensional (3D) hydrodynamic focusing sheaths a solution into a cylindrical core at the center of the channel, whereas twodimensional (2D) hydrodynamic focusing sheaths a solution into a columnar shape spanning the height of the channel.…”
mentioning
confidence: 99%
“…Mixers in microfluidics can be classified into groups of passive and active, where the second type needs an external energy supply . Forces resulting from acoustic, dielectrophoretic, electromagnetic, electrohydrodynamic, temperature gradient, and pressure perturbations are examples of external energies used to improve mixing in active mixers …”
Section: Introductionmentioning
confidence: 99%